Microemulsion mediated synthesis of triangular shape SnO2 nanoparticles: luminescence application - Luwang, Meitram Niraj (Applied Surface Science, 2014)
The triangular prism shapes of SnO2 center dot xH(2)O nanoparticles are prepared using microemulsion route. The effect of variation of water pool value on the formation of SnO2 nanoparticles was studied. There is the quantum size effect in absorption study of SnO2 nanoparticles. With the increase of the water pool value, there is a decrease in the band edge absorption energy suggesting the weak quantum confinement effect (QCE) in SnO2 nanoparticles. Quenching effect increases with increase of water to surfactant ratio in luminescence. There is no significant effect in lifetime values for SnO2 nanoparticles in both microemulsion and powder form. SnO2 nanoparticles show green emission due to oxygen vacancy. SnO2 nanoparticles when doped with Eu3+ ions give the enhanced luminescence of Eu3+ due to the surface mediated energy transfer from SnO2 to Eu3+ ion. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Microemulsion; Theoretical particle size calculation; Triangular nanoparticles